2018
DOI: 10.1158/1535-7163.mct-17-1124
|View full text |Cite
|
Sign up to set email alerts
|

BRAF Gene Copy Number and Mutant Allele Frequency Correlate with Time to Progression in Metastatic Melanoma Patients Treated with MAPK Inhibitors

Abstract: Metastatic melanoma is characterized by complex genomic alterations, including a high rate of mutations in driver genes and widespread deletions and amplifications encompassing various chromosome regions. Among them, chromosome 7 is frequently gained in -mutant melanoma, inducing a mutant allele-specific imbalance. Although amplification is a known mechanism of acquired resistance to therapy with MAPK inhibitors, it is still unclear if copy-number variation and mutant allele imbalance at baseline can be associ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 37 publications
2
22
3
Order By: Relevance
“…In melanoma patients, decreased BRAF allelic frequency is associated with a poorer clinical outcome to BRAF inhibition and combined BRAF/MEK inhibition (Lebbé et al, 2014;Stagni et al, 2018). The proposed mechanism behind this response is paradoxical MAPK pathway activation due to a higher wild-type allele frequency.…”
Section: Discussionmentioning
confidence: 99%
“…In melanoma patients, decreased BRAF allelic frequency is associated with a poorer clinical outcome to BRAF inhibition and combined BRAF/MEK inhibition (Lebbé et al, 2014;Stagni et al, 2018). The proposed mechanism behind this response is paradoxical MAPK pathway activation due to a higher wild-type allele frequency.…”
Section: Discussionmentioning
confidence: 99%
“…The wide peak annotated by HIPK2 and TBXAS1 contains 72 genes, including BRAF. BRAF amplification is a mechanism of acquired resistance to BRAF inhibitors in BRAFV600E melanomas [56,57,58,59]. We found that patients harboring BRAF-M and HIPK2/TBXAS1-A had shorter progression-free intervals (PFI) compared to patients harboring BRAF-M without HIPK2/TBXAS1-A (cox-ph P = 0.016, Table 4, Figure 5).…”
Section: Novel Melanoma Combinations Detected By Crsomentioning
confidence: 87%
“…Moreover, the choice and use of techniques able to quantify the mutant allele frequency of BRAF gene is important since it is reported to influence the clinical efficacy of the BRAF/MEK inhibitors treatments. So, quantitative analysis of the BRAF gene could be useful to select the melanoma patients who are most likely to benefit from target therapy (Stagni et al, 2018 ). In addition, intertumoral and intratumoral heterogeneity could lead to misinterpretation of BRAF mutational status; this is especially important if testing is performed on primary specimens, or micromestasis, when abundant metastatic lesions are unavailable.…”
Section: Discussionmentioning
confidence: 99%